GeCpbig2 [Cpbig = C5(CH2C6H4-iPr)5]: A Flexible Sandwich Molecule - Naglav, Dominik; Tobey, Briac; Harder, Sjoerd; Schnepf, Andreas (Zeitschrift für Anorganische und Allgemeine Chemie, 2013)
GeCp (1) [Cp = C (CHCH-iPr)] was synthesized by a reaction of KCp either with a GeCl solution or GeCl and was obtained as colorless crystals. The molecular structure of 1 was determined by X-ray diffraction, showing that 1 features two pentahapto bonded Cp ligands in a bent configuration with a Cp-Ge-Cp angle of 161°. Two out of ten benzyl substituents point towards the lone pair at the germanium atom so that two molecules fit perfectly together, leading to a dimeric arrangement of 1 within the solid state. Two polymorphs of 1 could be isolated, where 1 is oriented in a different way. As indicated by quantum chemical calculations, the open structure, where all benzyl substituents point away from the germanium atom is only disfavored by 21.6 kJ·mol. In the open structure a bent arrangement is still realized, giving access to the lone pair at the germanium atom for further applications, e.g. in coordination chemistry. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.